2022
DOI: 10.1177/20427530221117327
|View full text |Cite
|
Sign up to set email alerts
|

Digital learning and the lopsidedness of the education in government and private primary schools during the COVID-19 pandemic in West Bengal, India

Abstract: Since March 2020, all academic institutions have been closed due to the COVID-19 pandemic and have been encouraged online mode of education to the students in West Bengal, India. The most profound negative effect of the school closure has been noticed on primary education. This research examines how school closures in both government and private primary schools in West Bengal result in uneven teaching-learning opportunities in formal and non-formal education during the COVID-19 pandemic. The present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…But in developing countries like India, digital learning was a big challenge for many. Sarkar et al [17] observed a huge gap between private and govt. School.…”
Section: Conclusion and Recommenda-tionmentioning
confidence: 99%
“…But in developing countries like India, digital learning was a big challenge for many. Sarkar et al [17] observed a huge gap between private and govt. School.…”
Section: Conclusion and Recommenda-tionmentioning
confidence: 99%